A Comprehensive Study for Leveraging the Libraries Of Higher Educational Institutes For Career Guidance - Prasad, M. Srinivasa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
It is essential for a contemporary college in India to have a library that has been meticulously organised and is fully operational. This ensures that it can fulfil its role as the intellectual hub of the institution for both students and faculty. In the field of career guidance, libraries have the potential to play an important role. Within the context of formal education, the library is often referred to as the "heart of education." Higher education libraries are committed to providing students with an independent learning environment as part of their overall mission. In order to better serve their customers, many book stores and libraries have moved their collections of books into private homes. As a consequence of this, one can draw the conclusion that an efficient library system is essential to the success of career guidance programmes housed within educational institutions. Because of this, the educational system needs to improve its library system and do a better job of spreading information about various careers.